P881 Young patient with left ventricular hypertrophy and accidentally discovered aortic dissection: hypertensive heart or hypertrophic cardiomyopathy?. (17th January 2020) - Gawor, M; Franaszczyk, M; Kowalik, E; Spiewak, M; Michalowska, I; Grzybowski, J
Abstract: A 36-year-old male with positive family history of sudden cardiac death (his uncle"s son died suddenly at the age of 25), hospitalized a month ago in a local hospital due to acute hypertensive cardiogenic pulmonary edema, was referred to our institution for further evaluation with suspicion of hypertrophic cardiomyopathy. On admission patient was asymptomatic, without fatigue, exertional dyspnoea, chest pain or syncope. On physical examination his BP was significantly elevated (180/100 mmHg). The lungs were clear on auscultation, liver was not enlarged, jugular veins were normal, there was no oedema of lower extremities. Abdominal auscultation revealed vascular murmur in umbilical region. The baseline level of NT-proBNP was 811.4 (range 0–125) pg/mL, and high-sensitivity cardiac troponin T was 20.2 (range 0–14) ng/L. The standard 12-lead electrocardiogram demonstrated sinus rhythm, left atrial enlargement and left ventricular (LV) hypertrophy with nonspecific ST segment and T-wave changes (Fig. 1A). No significant pathology was present on chest X-ray (Fig. 1B). Transthoracic echocardiography revealed significant concentric LV hypertrophy with preserved LV ejection fraction (EF 70%) and moderately decreased global longitudinal strain (GLS-13.7%). There was mild dilatation of left atrium. Ascending aorta diameter was in normal range (Fig. 1C-D). Cardiac magnetic resonance (CMR) scan confirmed concentric LV hypertrophy with the maximal wall thickness of 18 mm at interventricular septum, and increased myocardial mass (LV mass index 124 ml/m2, range 59–92). Moreover, small areas of late gadolinium enhancement were found in LV segments (Fig. 1E-F). Due to presence of vascular murmur in abdomen, ultrasound imaging was performed. The exam revealed abdominal aortic dissection (Fig. 1G-H). Patient was transferred to the computed tomography (CT) unit to confirm the diagnosis. Aortic dissection originated below renal arteries and involving common illiac arteries was detected (Stanford B). The presence of thrombi within the lumen created by the aortic dissection suggested chronic presentation. Patient was managed conservatively with strict blood pressure control and close follow up arranged. We decided to perform genetic analysis. Currently we are awaiting the results in hope that it will help us to establish the diagnosis and differentiate hypertensive heart from hypertrophic cardiomyopathy. In conclusion, aortic dissection typically presents with tearing chest pain and severe hemodynamic compromise. Painless dissection, like in this case, is relatively rare. Differential diagnosis between hypertensive heart and hypertrophic cardiomyopathy is crucial as it has direct therapeutic impact.